Cocoa from agricultural resource to cultural tourism potential. Producers motivations in the north central area of Manabí, Ecuador - Félix Mendoza, Angel Guillermo (2021)
The situation of the production of cocoa in the province of Manabi (Ecuador) is presented, together with its development possibilities with the introduction of a sustainable cultural revaluation policy. Cocoa producers generally carry out their activities in rural areas and urban peripheries where living conditions are often precarious; each productive unit (farm) has an approximately extension of five hectares, and 90% of their maintenance is carried out by the family. The objective of this research was to identify the different groups of producers, based on their motivations, for the production of cocoa in the north central area of Manabi, Ecuador. The work comprised two stages: (1) exploratory, where data from official bodies was processed on the ARC GIS software; (2) field work, in which a Likert scale questionnaire was used. The sample is made up of 196 cocoa producers. The research design is flexible, with a quantitative and qualitative approach; exploratory in nature. There are two large groups of producers. The first set of producers related to the simple commercialization of cocoa and the second set of producers that shows a significant appropriation of the product as a reflection of the local culture. A positive context is glimpsed for initiatives around agricultural tourism.